Co-modification method of aluminide cladding coating

By introducing Si and Pt modified elements into the aluminide coating and adopting laser cladding technology, the problems of the existing aluminide coating decreased oxidation resistance and film peeling in high temperature environments are solved, and higher oxidation resistance and bonding strength are achieved.

CN119800351APending Publication Date: 2025-04-11HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510163384.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing aluminide coatings are prone to problems such as decreased oxidative resistance and film peeling in long-term service and high-temperature environments, resulting in reduced oxidative resistance.

Method used

The coating was prepared by using the co-modification method of aluminide cladding coating, by adding modified elements Si and Pt to the solid-phase cladding powder, and ethyl acetate to the liquid phase binder, and combining with the laser cladding process.

Benefits of technology

It significantly improves the oxidation resistance and peeling resistance of the aluminum coated coating, improves the oxidation resistance in high-temperature water vapor environment, and enhances the bonding strength between the coating and the base material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800351A_ABST
    Figure CN119800351A_ABST
Patent Text Reader

Abstract

The invention discloses a co-modification method of an aluminide cladding coating, which comprises the following steps: cleaning and preheating the surface of a workpiece to be plated, uniformly spraying cladding slurry onto the surface of the workpiece, naturally air-drying and curing at medium temperature, and finally, carrying out laser cladding to obtain the aluminide cladding coating, wherein the solid-phase cladding powder comprises the following components in percentage by mass: 50 to 70 percent of NiAl, 15 to 40 percent of Al, 0 to 5 percent of NH4Cl, 0 to 5 percent of Si and 0 to 5 percent of Pt. According to the co-modification method of the aluminide cladding coating, a prepared infiltrated layer is uniform in organization structure, moderate in thickness, sufficient in Al atom diffusion, good in metallurgical bonding with a matrix, not prone to falling off and suitable for austenitic steel and high-temperature alloy parts used for workpieces with the large length-diameter ratio and various complex shapes such as large boilers and oil and gas field conveying pipelines; and the method has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and in particular relates to a co-modification method of an aluminide cladding coating. Background Art

[0002] The corrosion of flow components with large aspect ratio used in high-temperature fields such as thermal power generation, energy storage, and petrochemicals has always been a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment. The operating costs and material costs caused by pipe blockages and pipe bursts due to oxide scale problems on the inner walls of flow components have increased by more than 20%.

[0003] Studies have shown that aluminide coatings have significant effects in solving the problems of component oxidation corrosion, wear, and high-temperature ablation. At present, the aluminide coatings developed by Xi'an Thermal Engineering Institute have shown excellent anti-oxidation service performance in the actual service process of the unit. However, with the extension of service time, the increase of unit power, and the complexity of the service environment, a single aluminide coating will inevitably face the phenomenon of decreased oxidation resistance and film peeling. In addition, after long-term service, the Al content of the film decreases, and the density and uniformity of the oxide film will also be lost, reducing the anti-oxidation performance of the coating. Therefore, it is necessary to develop a new type of anti-oxidation coating preparation technology and process with excellent oxidation resistance and anti-stripping ability, suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention

[0004] The object of the present invention is to overcome at least one of the above-mentioned disadvantages and to provide a co-modification method for an aluminide cladding coating, which is suitable for the preparation of anti-oxidation coatings on austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes.

[0005] To achieve the above object, the technical solution adopted by the present invention is a co-modification method of an aluminide cladding coating, comprising the following steps:

[0006] Step 1, weigh and prepare solid phase cladding powder and liquid phase binder according to proportion, and prepare cladding slurry after stirring and ball milling for use;

[0007] Step 2: Clean and preheat the surface of the workpiece to be plated, then spray the cladding slurry evenly onto the surface of the workpiece to be plated, and dry and solidify after spraying;

[0008] Step 3: Place the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, and obtain an aluminide cladding coating after cooling, and then perform cladding residue treatment.

[0009] In some embodiments of the present invention, in step 1, the infiltration source includes NiAl and Al, the modifier includes Si and Pt, the activator includes NH4Cl, and the binder includes ethyl acetate, wherein NiAl, Al, Si, and Pt powders are all sieved through a 1000-mesh sieve.

[0010] In some embodiments of the present invention, the preparation method of solid phase cladding powder is as follows: solid phase components are weighed according to mass percentage, including 50-70% NiAl, 15-40% Al, 0-5% NH4Cl, 0-5% Si and 0-5% Pt, and the total mass of the solid phase components is maintained at 100%. After weighing, the mixture is mixed by ball milling in a planetary ball mill at a ball milling speed of 350-400 rpm and a time of 12-24 h.

[0011] In some embodiments of the present invention, in step 1, the cladding slurry preparation method is as follows: the binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10-30% of the solid phase component, and after being fully stirred for 2-4 hours, it is placed in a planetary ball mill for ball milling mixing, and the ball milling speed is 350-400rpm and the time is 8-12 hours.

[0012] In some embodiments of the present invention, in step 2, the workpiece surface is pretreated by using a high-pressure water gun for cleaning and rinsing with alcohol or acetone; the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes;

[0013] In some embodiments of the present invention, in step 2, the thickness of the preset spray coating is 1-5 mm and the coating coverage is not less than 98%;

[0014] In some embodiments of the present invention, in step 2, the coating is dried by natural air drying for 24-48 hours, and the curing treatment is cured at 300-450° C. for 24-48 hours.

[0015] In some embodiments of the present invention, in step 3, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min; the residue is treated by flushing with a high-pressure water gun or high-pressure air flow, and naturally dried.

[0016] Compared with the prior art, the co-modification method of an aluminide cladding coating of the present invention also has at least the following beneficial effects:

[0017] 1. The present invention adds halide NH4Cl to the slurry components, which has the effect of promoting infiltration and activation, thereby improving the infiltration rate and the quality of the aluminide cladding coating;

[0018] 2. The present invention introduces modified elements Si and Pt into the solid phase powder, which can accelerate the oxide film transformation process and form an insoluble silicon oxide protective layer, thereby enhancing the oxidation and corrosion resistance of the aluminide cladding coating;

[0019] 3. The present invention prepares aluminide cladding coating by laser cladding process, which has concentrated heat, short action time, small thermal impact in cladding area, and high bonding strength between coating and parent material;

[0020] 4. The present invention prepares an aluminide cladding coating through an integrated laser cladding process production line. The aluminide cladding coating has high production efficiency, controllable thickness, high process repeatability, and is extremely practical and universal.

[0021] Furthermore, the addition of the modifying element Si can form a continuous SiO2 passivation film, improving the oxidation resistance and heat corrosion resistance.

[0022] Furthermore, the addition of the modifying element Pt can provide a channel for the Al element to form a dense oxide, inhibit or reduce the external diffusion of alloy elements, accelerate the transformation of θ-Al2O3 to α-Al2O3, improve the film-base bonding strength, effectively inhibit internal oxidation and internal sulfidation, and enhance the heat corrosion resistance of the aluminide cladding coating.

[0023] Furthermore, the segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-sectional morphology diagram of the aluminide cladding coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with relevant specific implementation methods.

[0026] The present invention provides a co-modification method for an aluminide cladding coating, comprising the following steps:

[0027] Step 1, weighing the solid phase components according to the mass ratio, including 50-70% NiAl, 15-40% Al, 0-5% NH4Cl, 0-5% Si and 0-5% Pt, specifically, NiAl and AL are infiltration sources, NH4Cl is an activator, Si and Pt are modifiers, wherein NiAl, Al, Si, Pt powders are sieved through a 1000 mesh sieve, and the total percentage of all solid phase components is kept at 100%; the weighed solid phase components are placed in a planetary ball mill at 350-400rpm for 12-24h to obtain a uniformly mixed powder, which is a solid phase cladding powder; then, ethyl acetate is added at a ratio of 10-30% of the mass of the solid phase components, wherein ethyl acetate is a binder, and after being fully mixed and stirred for 2-4h, it is placed in a planetary ball mill at 350-400rpm for 8-12h, and after completion, a uniformly mixed slurry is obtained, which is a cladding slurry.

[0028] Step 2, take out the workpiece to be plated, use a high-pressure water gun to clean the surface for 5-10 minutes to remove oil stains, dust, etc. on the workpiece surface and remove the oxide skin, and rinse it with alcohol or acetone to provide a neat and metallic surface for subsequent slurry spraying; then, preheat the workpiece at 200-250℃ for 30-60 minutes, spray the slurry to a suitable thickness at one time, and do not spray it in layers multiple times. Keep the spray layer thickness at 1-5mm and the coating coverage rate at least 98%. If the slurry layer is too thin, it will not provide sufficient penetration source, and if it is too thick, it will easily crack and peel off, affecting the uniformity of the penetration layer thickness; after spraying, let the workpiece air dry naturally for 24-48 hours, and then cure it at 300-450℃ for 24-48 hours. The segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of microcracks and tiny holes in the spray layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.

[0029] Step 3, the laser cladding process is as follows: laser power is 2-2.8KW, scanning rate is 20-40mm / s, spot diameter is 3-5mm, workpiece rotation speed is 0-5r / min, Ar gas flow is 15-20L / min; after completion, cool to room temperature and flush the surface residue of the workpiece with a high-pressure water gun or high-pressure air flow.

[0030] Through the above-mentioned processes and steps, a co-modification method of an aluminide cladding coating of the present invention prepares an aluminide cladding coating with a thickness of 0.85-1.75 mm and good metallurgical bonding under the conditions of adjusting main process parameters such as solid phase component content, modifier addition content, spray layer thickness and laser cladding parameters; the aluminide cladding coating obtained by the present invention has an oxidation resistance that is 19-65 times higher than that of the parent material in a 600°C pure water vapor environment and 20-78 times higher than that of the parent material in a 650°C pure water vapor environment, which can be explained that the aluminide cladding coating prepared by the method of the present invention effectively improves the oxidation resistance of the alloy parent material in a water vapor environment.

[0031] Example 1

[0032] Step 1. Weigh the solid phase components according to the mass ratio, including 50% NiAl, 40% Al, 2% NH4Cl, 4% Si and 4% Pt, place it in a planetary ball mill at 400 rpm for 12 hours to obtain a solid phase cladding powder; then, add 10% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0033] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes, and use spraying to pre-set the slurry layer thickness to 3mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.

[0034] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 20L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0035] The processes of Examples 2 to 9 are the same as those of Example 1. Examples 1 to 9 maintain the same solid phase components and liquid phase binder ratio. The specific laser cladding process conditions are detailed in Table 1. Table 1 is the specific parameters of Examples 1 to 9 of the method for improving the corrosion resistance of the aluminide cladding coating. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, aluminide cladding coatings with different thicknesses and Al atomic contents can be obtained.

[0036] Table 1

[0037]

[0038] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.85-1.75 mm. The specific results are shown in Table 1. The cross-sectional morphology of the infiltration layer is as follows: Figure 1 As shown in Table 1 and the cross-sectional morphology, it is found that the diffusion layer has a uniform structure, moderate thickness, sufficient diffusion of Al atoms, and a good metallurgical bond between the diffusion layer and the matrix, and is not easy to fall off.

[0039] Example 10

[0040] Step 1. Weigh the solid phase components according to the mass ratio, including 70% NiAl, 15% Al, 5% NH4Cl, 5% Si and 5% Pt, place it in a planetary ball mill at 350 rpm for 24 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0041] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 300°C for 48 hours.

[0042] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.5KW, a scanning rate of 20mm / s, a spot diameter of 2mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0043] Embodiment 11

[0044] Step 1. Weigh the solid phase components according to the mass ratio, including 50% NiAl, 40% Al, 5% NH4Cl and 5% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 8 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0045] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 30 minutes, and use spraying to pre-set the slurry layer thickness to 2mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 450°C for 48 hours.

[0046] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0047] Example 12

[0048] Step 1. Weigh the solid phase components according to the mass ratio, including 50% NiAl, 40% Al, 5% NH4Cl and 5% Si, place it in a planetary ball mill at 400 rpm for 12 hours to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0049] Step 2: Clean the surface of the workpiece with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 400°C for 48 hours.

[0050] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0051] Example 13

[0052] Step 1. Weigh the solid phase components according to the mass ratio, including 60% NiAl, 30% Al, 5% Si and 5% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0053] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 24 hours and cure it at 450°C for 48 hours.

[0054] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 30mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 18L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0055] Embodiment 14

[0056] Step 1. Weigh the solid phase components according to the mass ratio, including 65% NiAl, 25% Al, 2% NH4Cl, 4% Si and 4% Pt, place it in a planetary ball mill at 350 rpm for 12 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0057] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 4mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece for 36 hours and cure it at 450°C for 48 hours.

[0058] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 20L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0059] Embodiment 15

[0060] Step 1. Weigh the solid phase components according to the mass ratio, including 65% NiAl, 25% Al, 4% NH4Cl, 2% Si and 4% Pt, place it in a planetary ball mill at 350 rpm for 24 hours to obtain a solid phase cladding powder; then, add 20% ethyl acetate and stir it thoroughly for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0061] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.

[0062] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 4mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 15L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0063] Example 16

[0064] Step 1. Weigh the solid phase components according to the mass ratio, including 65% NiAl, 30% Al, 1% NH4Cl, 2% Si and 2% Pt, place it in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase cladding powder; then, add 30% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0065] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 24 hours, and cure it at 450°C for 48 hours.

[0066] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 35mm / s, a spot diameter of 4mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 18L / min; after completion, cool to room temperature and flush the residue on the workpiece surface with high-pressure airflow.

[0067] The co-modification method of the aluminide cladding coating in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. It has strong practicality, high permeation rate, excellent membrane-base bonding, and extremely good industrial mass production benefits.

[0068] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A co-modification method for an aluminide cladding coating, characterized in that: The following steps are involved: Step 1, weigh and prepare solid phase cladding powder and liquid phase binder according to proportion, and prepare cladding slurry after stirring and ball milling for use; Step 2: Clean and preheat the surface of the workpiece to be plated, then spray the cladding slurry evenly onto the surface of the workpiece to be plated, and dry and solidify after spraying; Step 3: Place the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, obtain an aluminide cladding coating after cooling, and perform cladding residue treatment.

2. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 1, the infiltration source includes NiAl and Al, the activator includes NH4Cl, the modifier includes Si and Pt, and the binder includes ethyl acetate; wherein NiAl, Al, Si, and Pt powders are all sieved through a 1000-mesh sieve.

3. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 1, the solid phase cladding powder preparation method is as follows: solid phase components are weighed according to mass percentage, including 50-70% NiAl, 15-40% Al, 0-5% NH4Cl, 0-5% Si and 0-5% Pt, and the total mass of the solid phase components is maintained at 100%. After weighing, they are mixed by ball milling in a planetary ball mill at a ball milling speed of 350-400rpm and a time of 12-24h.

4. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 1, the cladding slurry preparation method is as follows: the binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10-30% of the solid phase component, and after being fully stirred for 2-4 hours, it is placed in a planetary ball mill for ball milling mixing, and the ball milling speed is 350-400rpm and the time is 8-12 hours.

5. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 2, the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

6. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 2, the prefabricated slurry layer has a thickness of 1-5 mm and a coating coverage of not less than 98%.

7. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 2, the pre-coating is dried by natural air drying for 24-48 hours, and cured at 300-450° C. for 24-48 hours.

8. The co-modification method of an aluminide cladding coating according to claim 1, characterized in that: In step 3, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min.